Strengthening Tradition, Promoting National Health: Communal Jamu Drinking in Commemoration of Jamu Day 2025 - Wibowo, Teguh Setiawan; Sholihah, Maratush; Alma, Fatika Al Yasmin (Eastasouth Institute, 2025)
Jamu Day, commemorated annually on May 27th, is a crucial moment to reflect on Indonesia’s rich cultural heritage in traditional medicine. In 2025, a communal jamu-drinking activity was held as both a preservation effort of ancestral heritage and a public health campaign. This activity aimed to raise awareness of the benefits of jamu as a health drink made from natural ingredients. It also served as an educational platform to promote national self-reliance in maintaining health through traditional approaches. Through collective participation and a spirit of togetherness, the event emphasized that jamu is not only a cultural legacy but also a relevant preventive health solution in modern lifestyles.